2011
DOI: 10.1016/j.pedhc.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life in Children and Adolescents With Sickle Cell Disease

Abstract: Objective-To assess health-related quality of life (HRQOL) in children and adolescents with sickle cell disease (SCD).Design, Setting, and Participants-The PedsQL™ 4.0 Generic Scales, a multidimensional self-report instrument that has been shown to be valid and reliable for use in children and adolescents with chronic illness, consists of 23 items that assess physical, emotional, social, and school functioning. Questionnaires were administered to 124 children and adolescents (aged 8-18 years, child self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
96
3
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 26 publications
(41 reference statements)
15
96
3
6
Order By: Relevance
“…Prior studies confirmed that children with SCD had significantly impaired health related quality of life when compared to healthy children [2,5,8]. The quality of life of our patients were not only lower than healthy children but also very similar to those found in patients suffering from other chronic conditions such as cancer receiving treatment and rheumatoid arthritis [2,5,8].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Prior studies confirmed that children with SCD had significantly impaired health related quality of life when compared to healthy children [2,5,8]. The quality of life of our patients were not only lower than healthy children but also very similar to those found in patients suffering from other chronic conditions such as cancer receiving treatment and rheumatoid arthritis [2,5,8].…”
Section: Discussionsupporting
confidence: 82%
“…It is a severe chronic diseases associated with continuous treatment over an extended period of time, and significant human suffering [2]. It is well known that all chronic and acute complications of SCD could be expected to have a negative impact on quality of life of the patients, especially for children and adolescent [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations